Electric spring average model development and dynamic analysis for demand‐side management. Issue 2 (25th February 2020) - Areed, Emad Fuad; Abido, Mohamed A.; Al‐Awami, Ali T.; Hussain, Syed Asim
Abstract : This study proposes a new averaged model for steady‐state and dynamic response analysis of the electric spring (ES). The accuracy of steady‐state and dynamic behaviour of the ES is demonstrated. Further, the dynamic behaviour of the proposed model is described as a function of the modulating signal. The developed model is used to design a controller for bus voltage regulation in a distribution system with an intermittent renewable energy source. The ES controller design problem is formulated as an optimization problem with a time domain‐based objective function to reduce the time‐weighted voltage deviations using particle swarm optimization method. Different disturbances have been applied to verify the developed ES model accuracy including sudden changes in renewable source current and load variations. An experimental analysis is also performed with the detailed non‐linear switching model of the ES to verify its behaviour with that of the proposed averaged model. The characteristics and performance of ES are thoroughly investigated. The effectiveness of the developed model and the proposed controller design approach is demonstrated in terms of a significant improvement in the dynamic performance of the distribution system